Incentivizing wellness through community supported agriculture - Jairus Rossi (Thomas A. Lyson Center for Civic Agriculture and Food Systems, 2021)
Community supported agriculture (CSA) programs are emerging as popular consumer options for produce acquisition. While many researchers have discussed the impacts of CSA on economies, communities, and the environment, others are interested in documenting how produce-based CSA shapes health. In this paper, we evaluate whether and to what extent CSA incentive programs, funded by diverse employer groups in central Kentucky 2015–2018, impact shareholder wellness. To evaluate impact, we use two distinct types of data: we compare shareholders’ perceived frequency of food lifestyle behaviors from pre- and post-season surveys, and we examine anonymized medical claims from a subset of these participants to determine if CSA participation impacts short-run usage of medical services. From survey data, we observed statistically significant changes in some shareholder behaviors. For instance, CSA shareholders perceived that they consumed vegetable salads more often while decreasing their intake of processed foods and snacks. From medical claims data, shareholders are billed less in diet-related medical claims following CSA participation compared to a control group from the same employer organization. In short, we find that CSA is generally beneficial and participants view their experience as providing motivation to reshape their relationship to food. We conclude by offering strategies for institutions and organizations to effectively develop and support CSA incentive programs.